JÚZIW SHEBERLIGIN HÁM NÁTIYJELILIGIN ASIRIWDA TRENIROVKA PROCESSIN REJELESTIRIWDIŃ ÁHMIYETI - Ramazanov, M.B. (SCIENCE and SOCIETY, 2023)
The article is devoted to the selection of young talented swimming athletes, their orientation to the swimming style, taking into account their anatomical features and physiological capabilities.